Better response to Tanreqing injection in frequent acute exacerbation of chronic obstructive pulmonary disease (AECOPD) patients—Real-world evidence from a nationwide registry (ACURE) study - Fan, Guohui; Wang, Dingyi; Wu, Sinan; Li, Demin; Ren, Xiaoxia; Dong, Fen; Huang, Kewu; Chen, Yahong; Zhang, Hongchun; Wang, Chen; Yang, Ting (Frontiers in Pharmacology, 2023)
Objective To systematically investigate the efficacy of Tanreqing (TRQ) injection on in-hospital outcomes among inpatients with frequent or infrequent AECOPD. Methods In this ongoing, nationwide multicenter registry designed to investigate clinical characteristics, management and prognoses of Chinese patients admitted for AECOPD in real-world settings, we collected characteristics, comorbidities, in-hospital prognoses, and information on the COPD assessment test (CAT) questionnaire, PEACE questionnaire and modified British Medical Research Council (mMRC) questionnaire from each enrolled patient. Frequent AECOPD was determined as being admitted to hospital ≥ 1 time or visited emergency room (ER)≥ 2 times due to AECOPD within a year. A propensity match method and univariable and multivariable regression models were performed to analyze the efficacy of TRQ on clinical outcomes for inpatients with frequent AECOPD. Results A total of 4135 inpatients were involved in analysis, including 2179 administered with TRQ and 1956 not. Among those administered with TRQ, 493 had frequent AECOPD and 358 had infrequent AECOPD. After propensity score match, a significant reduction of CAT score at discharge (TRQ median 12, IQR 8.0-16.0; non-TRQ median 13, IQR 9.0-18.0, p=0.0297) and lower rate of ICU admission (TRQ 0.8% Vs non-TRQ 2.6%, p=0.0191) and shorter length of stay (LOS) (TRQ median 11, IQR 9.0-14.0; non-TRQ median 11, IQR 8.0-14.0, p=0.004) were observed in TRQ group, compared with non-TRQ group among frequent AECOPD patients. In subgroup analysis, those with PEACE score > 7 on admission, TRQ contributed to significantly lower CAT score at discharge (p=0.0084) and numerically lower ICU admission rate with marginal statistical significance. Among those with phlegm-heat symptom complex on admission ≥ 2, lower CAT score at discharge and lower ICU admission were also observed in TRQ group. Conclusion TRQ injection had better efficacy in patients with frequent AECOPD in reducing ICU admission and alleviating respiratory symptoms, especially those with especially for those with higher severity on admission or more phlegm-heat symptoms.